Kant’s Political Theodicy - Shell, Susan Meld (Con-Textos Kantianos. International Journal of Philosophy, 2026)
Scholarship on Kant’s religious writings commonly diverges on two related issues: the theological weight and meaning of his endorsement of religious faith, and the apparent inconsistency between his earlier and later, seemingly less secular, treatments of the subject. The questions raised by these disputes are not only theoretical; for at stake is whether in Kant’s considered view a just political community is ultimately sustainable without affirmative theological commitments of some kind.Kant’s brief essay “On the Failure of All Philosophic Efforts at Theodicy” opens a promising window on such questions. It is thematically continuous with the Critique of Judgment, published one year earlier, that itself ends with an implicit proof of the impossibility of theodicy understood as a theoretical justification of God’s moral wisdom based on what experience of the world teaches. [8:255] At the same time, Kant’s essay also differs from the Critique of Judgment in in a number of crucial ways that partly reflect Kant’s darkening assessment of his political circumstances as ones requiring new means of public enlightenment on the crucial question of the true basis of religious faith, as reflected in subsequent religious writings beginning with Religion within the Boundaries of Bare Reason. One striking feature of that change is the replacement of sincerity, or honesty before the bar of conscience, with conscientiousness, or striving to be honest, as the highest goal of moral aspiration, and of indulgence of the inclinations through self-deception as the ultimate source of human evil. Another is conceptual room for something like grace in the religious sense.